2012
DOI: 10.1586/erm.12.24
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive fetal trisomy 21 detection using chromosome-selective sequencing: a variation of the molecular counting theme

Abstract: Fetal DNA is present in the plasma of pregnant women. A fetus with trisomy of a chromosome will release an increased amount of DNA from that chromosome into maternal plasma. Such an increase has previously been measured using methods that allow individual DNA molecules to be counted. One such method involves the use of random massively parallel sequencing of maternal plasma DNA. As the sequencing process is random, sequence tags from a potentially aneuploid chromosome only represent a fraction of the sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Studies found that NIPT technology can detect microdeletions and microduplications greater than 300 Kb in fetal genomes . This study successfully used NIPT to detect microdeletions of about 5 Mb in fetal chromosome 15, which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 89%
“…Studies found that NIPT technology can detect microdeletions and microduplications greater than 300 Kb in fetal genomes . This study successfully used NIPT to detect microdeletions of about 5 Mb in fetal chromosome 15, which is consistent with the literature.…”
Section: Discussionsupporting
confidence: 89%
“…We have known that it is very e cient and accurate for the detection of common fetal chromosome aneuploidy, especially for chromosome 13, 18 and 21. Recently, some studies have found that NIPT through deeper sequencing can screen some microdeletions and microduplications, which are greater than 300 Kb in fetal genomes [18][19][20][21][22] . However, there are no reports of 17q12 duplication syndrome screened by NIPT previously.…”
Section: Discussionmentioning
confidence: 99%
“…However, DS could only be detected in samples containing 25% fetal DNA [ 83 ]. If a 25% fetal enhancement is achieved, 7,680 molecules would need to be analyzed to achieve successful characterization of trisomy status [ 84 ]. Evans et al reported that if fetal DNA is enriched to 20%, then 2,609 counts would be sufficient to achieve a 99% DR for a 1% FPR.…”
Section: Further Developmentsmentioning
confidence: 99%